2021
DOI: 10.1093/g3journal/jkab218
|View full text |Cite
|
Sign up to set email alerts
|

The amino acid substitution affects cellular response to mistranslation

Abstract: Mistranslation, the mis-incorporation of an amino acid not specified by the “standard” genetic code, occurs in all organisms. tRNA variants that increase mistranslation arise spontaneously and engineered tRNAs can achieve mistranslation frequencies approaching 10% in yeast and bacteria. Interestingly, human genomes contain tRNA variants with the potential to mistranslate. Cells cope with increased mistranslation through multiple mechanisms, though high levels cause proteotoxic stress. The goal of this study wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 83 publications
0
24
0
Order By: Relevance
“…Other factors are extrinsic to the tRNA. These include the number of competing tRNAs that buffer the mistranslating tRNA (Zimmerman et al 2018), the environment in which cells expressing the mistranslating tRNA (Berg et al 2021b) are found and the genetic background of the organism. Genetic background contributes to the impact of a mistranslating tRNA in numerous ways.…”
Section: Each Point Represents One Biological Replicatementioning
confidence: 99%
See 3 more Smart Citations
“…Other factors are extrinsic to the tRNA. These include the number of competing tRNAs that buffer the mistranslating tRNA (Zimmerman et al 2018), the environment in which cells expressing the mistranslating tRNA (Berg et al 2021b) are found and the genetic background of the organism. Genetic background contributes to the impact of a mistranslating tRNA in numerous ways.…”
Section: Each Point Represents One Biological Replicatementioning
confidence: 99%
“…Peptides were analyzed on a hybrid quadrupole orbitrap mass spectrometry (Orbitrap Exploris 480; Thermo Fisher Scientific) equipped with an Easy1200 nanoLC system (Thermo Fisher Scientific) as previously described in Berg et al (2021b).…”
Section: Mass Spectrometrymentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is not clear that HSF1 is a regulatory factor in the amino acid starvation response. Furthermore, the cellular response to mistranslation is affected by which amino acid is being mistranslated - for example, yeast cells carrying a tRNA that substitutes serine for arginine results in a heat shock response, but proline to alanine substitution results in a minimal heat shock response [20]. Thus, the amino acid stress imposed by arginine deprivation and canavanine may be a specific response due to the inherent properties of arginine rather than an example of a more general toxic amino acid analog response.…”
Section: Introductionmentioning
confidence: 99%